Programmed cell death in the cognitive impairment of obstructive sleep apnea - Yanru Ou; Xiufang Wang; Dandan Zong; Ruoyun Ouyang (Cell & Bioscience)
Abstract Cognitive impairment (CI) is a significant and extraordinary complication of obstructive sleep apnea (OSA) patients. Programmed cell death (PCD) is an active and ordered process regulated by genes. A growing number of studies find that PCD is responsible for cognitive dysfunction and plays an important role in various neurological diseases, which involve apoptosis, necroptosis, pyroptosis, ferroptosis, and cell death associated with autophagy. However, the influence of PCD on OSA-CI remains unclear. We summarized the relevant studies that discussed the involvement of PCD in the CI of OSA and aimed to clarify the underlying mechanisms. Intermittent hypoxia (IH)-induced PCD had a critical effect on the mechanisms that produced the ultimate neurological deficit in OSA, and the PCD involved mainly included apoptosis, autophagy, ferroptosis, and pyroptosis. IH regulates PCD directly or through specific pathways, and drugs targeting related molecules have the potential to improve cognitive function. These findings enrich the pathogenesis of OSA-CI and provide new therapeutic insights.